Agro-morphological Characterization of Corchorus olitorius Cultivars of Benin - ADEBO, Habib; AHOTON, ESSÈHOU LÉONARD; QUENUM, FLORENT JEAN-BAPTISTE; EZIN, VINCENT (My University, 2015)
Aim: Corchorus olitorius is indubitably one of the most important vegetables in Benin. It is grown in most regions of the country and also in the tropical and sub-tropical regions of the world, particularly in Asia, Africa and Latin America. Therefore, the aim was to determine the phenotypic diversity of different cultivars of C. olitorius in Benin Study Design: A randomized complete block design was used. Methodology: Forty seed samples of C. olitorius were collected during a survey carried out in twenty-one (21) municipalities of Benin. These seeds were sown at Savè in the center of Benin. Twelve (12) quantitative traits and eleven (11) qualitative traits were recorded. Results: The results of principal component analysis and hierarchical ascending classification applied to quantitative variables showed six (06) classes of cultivars namely: C1, C2, C3, C4, C5 and C6. The discriminating characteristics highlighted were: plant height, number of leaves per plant, number of branches per plant, leaf length, leaf width, fruit length, fruit diameter, flowering Original Research Article date, the number of days between two successive cuts and fresh leaf weight. For cultivars of classes C5 and C4, the number of days between two successive cuts was the shortest and their cycle was the longest. Fresh leaf weight and fruit number per plant were higher. As for the qualitative characters studied, only four cultivars showed variability. Three (03) leaf types were identified: lobed type, lanceolate type and simple indented type. Conclusion: There is a great variability within Benin cultivars. Cultivars from southern Benin were more diverse than those in the north. Cultivars of the classes C5 and C4 showed the best performance (important number of leaves and branches, high yield and a big size). These two classes are of great importance to vegetable farmers and breeders. Cultivars of classes C1 and C3 are of less importance.
Keywords: Corchorus olitorius; morphotype; characterization; multivariate analysis; diversity; Benin.